PEMBERDAYAAN APARATUR SIPIL NEGARA DALAM MENINGKATKAN KINERJA PEGAWAI DINAS KEHUTANAN PROVINSI KALIMANTAN TIMUR - David Benyamin (Jurnal Administrative Reform, 2019)
The purposes of this research are to describe and analyze The Empower of Apparatus Source in Increasing Employees’ Enthusiasm. The research focuses on some aspects in empowering of apparatus in Dinas Kehutanan Provinsi Kalimantan Timur. This research used the qualitative research method by employing interview and document analysis as the data collection techniques. The data analysis used in this research was the interactive analysis model from Miles and Huberman. The results of this study explains that, from the 14 indicators specified results are less than optimal as many as 10 indicators that do not meet achievement targets. Keyword: empower of apparatus, employees’ enthusiasm.